Penggunaan Data Mikrotremor Dan Vs30 Untuk Mengetahui Hubungan Ketebalan Sedimen Terhadap Produktivitas Kelapa Sawit Dan Implementasinya Dalam Pembelajaran Fisika - Riska Marwanti; M.Lutfi Firdaus; M Farid (PendIPA Journal of Science Education, 2017)
The aims of this study were to determine the relationship of sediment thickness to palm oil productivity and to know the improvement of student learning outcomes after learning using LKPD based on service learning. This study was conducted using HVSR (Horizontal to Vertical Spectral Ratio) method. Data were collected as 10 primary data points, while secondary data on palm oil productivity was obtained from PT Bio Nusantara Teknologi. Data obtained from field measurements are numerical data of natural wave recording or seismic signal at each measurement point. The data is processed using Geopsy software so it can be known the price of the dominant frequency (fo), while the shear wave velocity (Vs30) is obtained through USGS data. The result of this research is there is intermediate relationship between sediment thickness to productivity of palm oil with product moment correlation value equal to 0,6392, so that thicker layer of sediment hence higher productivity. The results of this study further used as a source of information contained in the form of LKPD-based service learning to become a learning medium taught by Problem Based Learning (PBL) model on students of class XI SMK N 1 Padang Jaya to know the improvement of students' cognitive learning outcomes in physics learning. The result of research implementation influence of sediment thickness to productivity of palm oil in classroom study showed cognitive learning result of learners experience improvement of cognitive learning result with average value of N-gain of 0,52 (medium criterion).